Contraception and abortion in times of crisis: results from an online survey of Venezuelan women - Stifani, Bianca M.; Luigi, Genesis; Tam, Genevieve; Zamberlin, Nina; Carino, Giselle; Medina-Salas, Susana; Fetters, Tamara; Gill, Roopan (Frontiers in Global Women's Health, 2023)
Introduction In the last decade, Venezuela has experienced a complex humanitarian crisis that has limited access to healthcare. We set out to describe Venezuelan women's experiences accessing sexual and reproductive health services, including abortion, which is heavily restricted by law. Methods We fielded an online survey in July of 2020 among Venezuelan women recruited through social media advertisements. We conducted descriptive statistical analyses using Excel and STATA SE Version 16.0. Results We received 851 completed survey responses. Almost all respondents experienced significant hardship in the last year, including inflation (99%), worries about personal safety (86%), power outages (76%), and lack of access to clean water (74%) and medications (74%). Two thirds of respondents used contraception in the last two years, and almost half (44%) of respondents had difficulty accessing contraception during that same time period. About one fifth of respondents reported having had an abortion; of these, 63% used abortion pills, and 72% reported difficulties in the process. Half of those who had an abortion did it on their own, while the other half sought help – either from family members or friends (34%), from providers in the private health sector (14%), or from the Internet (12%). Conclusions Venezuelan women who responded to our survey describe a harsh context with limited access to sexual and reproductive health services. However, they report relatively high rates of contraceptive use, and abortion seems to be common despite the restrictive legal setting.